Structure and Physical Properties of EVA/Starch Precursor Materials for Foaming Applications - Rodriguez-Perez, M. A.; Simoes, R. D. [UNESP]; Constantino, C. J. L. [UNESP]; de Saja, J. A. (Wiley-Blackwell, 2011)
The use of biodegradable materials to develop polymeric blends visioning distinct applications is desirable and nowadays is an important research field. In this work, blends of an ethylene-vinyl acetate copolymer (EVA) and 30, 50, and 70% in weight of an unmodified corn starch have been successfully fabricated. The structure of these blends have been characterized using scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR). It was found that the original starch particles are kept in the blends forming a separate phase from EVA. The FTIR confirmed that EVA and starch comprise a physical mixture in the blends. Besides, the blends were found very homogenous and mainly amorphous with the EVA melting temperature being independent of the starch content. The melt flow index (MFI) decreased for higher contents of starch, revealing that starch acts as a filler in the blends. Physical properties such as density, hardness, and thermal conductivity were found to increase with the content of starch in the blends. Considering one of the goals of this research, which is producing foams using these blends as precursor materials, the structural and physical characteristics determined here are very satisfactory and open good perspectives in this sense. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 121: 2324-2330, 2011
Keywords: blends; EVA; starch; mechanical properties; thermal properties